Association Between Arterial Stiffness and Blood Pressure Progression With Incident Hypertension: A Systematic Review and Meta-Analysis - Saz-Lara, Alicia; Bruno, Rosa María; Cavero-Redondo, Iván; Álvarez-Bueno, Celia; Notario-Pacheco, Blanca; Martínez-Vizcaíno, Vicente (Frontiers in Cardiovascular Medicine, 2022)
Background Arterial stiffness is an independent predictor of cardiovascular and all-cause mortality that is classically regarded as a consequence of arterial hypertension. However, a growing number of studies have shown that arterial stiffness is involved in the pathogenesis and prognosis of arterial hypertension. Thus, in this systematic review and meta-analysis, we aimed to assess whether arterial stiffness, as measured by pulse wave velocity, systolic blood pressure and diastolic blood pressure are associated with incident hypertension. Methods The Scopus, PubMed, Web of Science and Cochrane Library databases were searched from inception to March 30, 2021. The DerSimonian and Laird method was used to compute pooled relative risk estimates and their respective 95% confidence intervals of association between incident hypertension with pulse wave velocity, systolic blood pressure and diastolic blood pressure. Results Our findings provide a synthesis of the evidence supporting that the higher arterial stiffness (RR: 1.09; 95% CIs: 1.05, 1.12), systolic blood pressure (RR: 1.08; 95% CIs: 1.05, 1.10) and diastolic blood pressure (RR: 1.08; 95% CIs: 1.04, 1.12) are associated with incident hypertension in normotensive adult subjects, with similar independent predictive values. However, our results should be interpreted with caution because the meta-analyses performed showed considerable heterogeneity. Conclusions Our results showed that higher pulse wave velocity, systolic blood pressure and diastolic blood pressure are associated with incident hypertension. These findings are of clinical importance, supporting arterial stiffness as an additional tool for the prevention of arterial hypertension and being a fundamental component to reduce cardiovascular morbidity and mortality. Systematic Review Registration This study was registered in PROSPERO https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=236435 (Registration number: CRD42021236435).